'A Clash of Titans': Big Business and the Congo Reform Movement. Issue 374 (20th October 2021) - Clay, Dean
Abstract: The Congo Reform Association was the central focus of the Congo reform movement in Britain that sought to end Leopold II's hold on the Congo Free State. Through an examination of the personal correspondence and official publications of the Association and its members, this article examines the motivations of the business interests involved in the Association. First, it analyses the motivations of two of the key figures involved in the Association, E. D. Morel and John Holt, and emphasises that their reform activism was not informed by their apparent altruism. Second, it examines the clash between Holt and a pro‐Congo business adversary in Liverpool, Sir Alfred L. Jones, to highlight the influence of business interests in the reform movement. The question of the motivations of those who engage in humanitarian endeavours is one of many factors in the debates about the history of humanitarianism and human rights. This article attempts to answer this question using the Congo reform movement in Britain as a means through which to unpack these motivations, showing that humanitarian activism was informed by personal business interests as well as moral concerns.